Connection between lung deposited surface area (LDSA) and black carbon (BC) concentrations in road traffic and harbour environments. (1st March 2022) - Lepistö, Teemu; Kuuluvainen, Heino; Lintusaari, Henna; Kuittinen, Niina; Salo, Laura; Helin, Aku; Niemi, Jarkko V.; Manninen, Hanna E.; Timonen, Hilkka; Jalava, Pasi; Saarikoski, Sanna; Rönkkö, Topi
Abstract: Black carbon (BC) is one of the main components of ambient particulate matter. Previous studies have suggested that BC is more toxic than PM2.5 (mass concentration of all sub-2.5 μm particles). One possible reason for the greater toxicity is that BC is typically in a size range which penetrates easily into lung alveoli and BC particles have a large surface area due to their fractal structure. Due to these properties, toxic gaseous compounds can condensate on the surface of BC particles and then be transported effectively into human lungs, causing a large lung-depositing surface area (LDSA) of particles. In this study, we investigated the relationship between BC and LDSA concentrations in street canyon, highway, and harbour environments in the Helsinki Metropolitan area. In all the studied environments, BC and LDSA concentrations were strongly correlated. In the harbour, cases where marine traffic was considered as the main emission source, the average LDSA per BC mass was 2.4–2.7 times higher than in the road traffic environments. This result was linked to a larger lung depositing size of BC, suggesting that condensation and coagulation of other co-emitted compounds can have a major role in the lung deposition of BC. Thus, BC emissions from marine traffic can cause higher exposure of other co-emitted toxic compounds in the human lungs than the road traffic. The fraction of LDSA linked to BC emissions in the street canyon, the highway, and the harbour were 33%, 30%, and 47%, respectively, whereas the fractions of BC mass in PM1 concentration were 14%, 14%, and 7%, respectively. The results show that BC emissions contribute much more to LDSA than to mass concentration, which indicates that the possible strong negative health effects linked to ambient BC mass concentration could be related to the high LDSA concentration. Highlights: Characteristics of LDSA investigated in a harbour and near traffic in Helsinki area. BC emitted from marine traffic is linked to higher LDSA per mass than road traffic. BC emissions contribute more to LDSA (30–47% of total LDSA) than to PM1 (7–14%). In the harbour, higher absorption Ångström exponent was connected to higher LDSA. Health hazard of BC might be related to high LDSA and other co-emitted species.